Pendampingan Pembuatan Motif Batik Dengan Teknis Colet Di Karang Taruna Jangli Semarang: Assistance in Making Batik Motifs Using the Dabbling Technique at Karang Taruna Jangli Semarang - Anisi, Yunus; Mariana, Novita; Handayani UN, Dewi; Retnowati, Retnowati (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Semarang City is the Capital of Central Java Province, Indonesia which has a lot of potential in terms of culture, tourism, and geographical location. In terms of culture, Semarang has traditional dances such as Gambang Semarang and batik art. The colet batik motif is a technique for making batik that emerged along with the use of chemical dyes for batik. In order to introduce this technique further, mentoring was carried out for youth in the Jangli village cadet youth group by introducing the dab technique as an alternative in making batik motifs with natural dyes. The aim is to develop creativity and potential in order to be able to produce batik commodities that are unique in terms of batik motifs. The goal to be achieved is to cultivate the use of natural dyes in decorating and blocking fabric colors. This service activity was declared successful according to plan, which can be seen based on the involvement of participants and their enthusiasm while participating in the activity and can produce ethnic motifs with the dab technique to the dyeing process with natural dyes